(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The qualities of agricultural soil and water are diminishing continuously due to the rigorous anthropogenic activities currently stocking the soil with a lot of toxic chemicals including heavy metals. Heavy metals are highly persistent and non-biodegradable, control of their contamination is very tricky to handle. Their presence in soil and water is detrimental to food crops and humans. Various sources of heavy metals contaminants and the role of urban food production on human heavy metal contamination were discussed.Heavy metals have their way into the soil and food crops through wastewater irrigation and production in contaminated soil. The habitual heavy metals contamination sources for food crops are wastewater irrigation, abuse of agrochemicals, production in the contaminated field, atmospheric deposit when foods are exposed to contaminated air, and unethical mining activities. Agricultural soil in urban and peri-urban areas are heavily contaminated with heavy metal due to various anthropogenic activities. Wastewater irrigation intensify the contamination by supplying the soil with more heavy metals. The heavy metals are passed to food during production and subsequently to humans after consumption.